Particle size distribution of radioactive aerosols after the Fukushima and the Chernobyl accidents - Malá, Helena; Rulík, Petr; Bečková, Vera; Mihalík, Ján; Slezáková, Miriam (Journal of environmental radioactivity, 2013)
Following the Fukushima accident, a series of aerosol samples were taken between 24th March and 13th April 2011 by cascade impactors in the Czech Republic to obtain the size distribution of (131)I, (134)Cs, (137)Cs, and (7)Be aerosols. All distributions could be considered monomodal. The arithmetic means of the activity median aerodynamic diameters (AMADs) for artificial radionuclides and for (7)Be were 0.43 and 0.41 μm with GDSs 3.6 and 3.0, respectively. The time course of the AMADs of (134)Cs, (137)Cs and (7)Be in the sampled period showed a slight decrease at a significance level of 0.05, whereas the AMAD pertaining to (131)I increased at a significance level of 0.1. Results obtained after the Fukushima accident were compared with results obtained after the Chernobyl accident. The radionuclides released during the Chernobyl accident for which we determined the AMAD fell into two categories: refractory radionuclides ((140)Ba, (140)La (141)Ce, (144)Ce, (95)Zr and (95)Nb) and volatile radionuclides ((134)Cs, (137)Cs, (103)Ru, (106)Ru, (131)I, and (132)Te). The AMAD of the refractory radionuclides was approximately 3 times higher than the AMAD of the volatile radionuclides; nevertheless, the size distributions for volatile radionuclides having a mean AMAD value of 0.51 μm were very close to the distributions after the Fukushima accident.
Keywords: Chernobyl accident; zirkonium; Iodine Radioisotopes; monitorování radiace; AMAD; Cesium Radioisotopes; Fukushima Nuclear Accident; Chernobyl Nuclear Accident; Radiation Monitoring; radionuklidy; radioaktivní látky znečišťující vzduch; Radioisotopes; havárie elektrárny Fukušima; velikost částic; radioizotopy jodu; Air Pollutants, Radioactive; radioizotopy cesia; Zirconium; Aerosol size distribution; ruthenium; Fukushima accident; černobylská havárie; Ruthenium; Particle Size